Structural characterization of selectively grown multilayers with new high angular resolution and sub-millimeter spot-size x-ray diffractometer - Décobert, J.; Guillamet, R.; Mocuta, C.; Carbone, G.; Guerault, H. (Journal of Crystal Growth, 2013)
This paper reports the latest improvements performed on structural characterization by high resolution x-ray diffraction (XRD) on InGaAlAs-based multiple quantum well (MQW) structures on InP substrates, produced by metal organic vapor phase epitaxy in the regime of selective area growth (SAG). A new diffractometer, with a sub-millimeter x-ray spot, was used in the laboratory to study the MQW properties specifically in the SAG area. The results were compared to those obtained with a much smaller beam size using synchrotron radiation-based XRD. We show that a unique diffraction curve measured with the first setup fits the summation of a series of diffraction curves taken with the second setup in the cross section of the SAG area. More interestingly, applying some deconvolution criteria on this curve, a diffraction curve corresponding to the center of the mask area could be calculated and compared to the corresponding one taken among the second series. The excellent agreement between those curves proves that precious information of structural properties (such as strain and thickness) of the MQW in the center of the SAG area can be obtained from laboratory based measurements.
Keywords: A1. High resolution x-ray diffraction; A3. Metalorganic vapor-phase epitaxy; A3. Quantum wells; A3. Selective epitaxy; B2. Semiconducting iii-v materials